Design and Development of a Micro-Based Fuzzy Logic Temperature Controller for Portable Cooler - Mohd Hanafi, Abdul Halim (2007)
High demand to store breast milk, vaccines or other perishable items in developing communities is encouraging the development of portable cooler box. Portable cooler box also provides new way to store perishable items in remote locations. Furthermore, it believes that in the long term, fuzzy logic temperature control cooler box prove to be advantageous alternatives to the existing systems such as On-Off and PID controller cooler box. Due to this reason, portable cooler box with fuzzy logic temperature control is developed in this research. An attempt has been made to control the temperature of thermoelectric cooler (TEC) box by using Fuzzy Logic Control (FLC). The TECs operate on DC current and can control the cooling temperature by adjusting the value of DC current through thermoelectric. The MC68HC711E9-EVBU provides a low-cost and high-performance solution for TEC control. Earlier systems used many analog circuits to perform temperature control. The use of MC68HC711E9-EVBU allows the task to be handled by software. The suitable fuzzy rule has been prepared and implemented to control the temperature. In this research, a minimum hardware required due to the advanced capabilities of the processor. It is observed that the response of the FLC is faster than the conventional controller. In this work, a systematic design approach for the implementation of a microcontroller based data logger for recording the FLC variables is presented. The developed portable cooler box in this research can be used to maintain the temperature of the cooler at 15oC, thereby making it suitable for breast-feeding milk storage for 24 hours. Furthermore, the proposed system has been intentionally developed for the user convenience due to its portability and low power consumption.